Subglacial and underground structures detected from recent gravito-topography data - Klokočník, J. (Jaroslav); Kostelecký, Jan; Cílek, Václav; Bezděk, Aleš (Cambridge Scholars Publisher, 2020)
Data on gravity reveal a fascinating world of otherwise hidden phenomena, allowing us to ""see"" under the glaciers or beneath the sands. This book deals with subglacial areas like Antarctica and Greenland, as well as providing insights into features present under the sands of the Sahara (such as paleolakes) or at the ocean bottom (including a putative impact crater possibly related to the biblical flood). It analyses both static and variable gravity fields, and will help to distinguish the areas in which oil and gas can be found with higher probability. The book will be of interest to geoscie.